Phytoremediation of palm oil mill effluent (POME) by using Lemna minor and Chlamydomonas for organic fertilizer - Kamyab, Hesam (2015)
Malaysia is one of the major palm oil producer in the world. Therefore, it is important to develop environmental friendly and economic method for treating palm oil mill effluent (POME) in Malaysia. Nowadays, macrophytes and microalgae have received lot of attention due to its ability of removing pollutants. The main aim of this study is to investigate the potential of Lemna minor and Chlamydomonas for the bioremediation of palm oil mill effluent in order to achieve higher water quality standard and further to produce organic fertilizer. In this study, three different experiments were conducted starting with Lemna minor, followed by Chlamydomonas and finally in combination of Lemna minor and Chlamydomonas. The parameters tested are COD, nitrate, ammoniacal nitrogen, phosphate, MLSS, MLVSS, and nutritional content as organic fertilizer. The result showed that a maximum of 25.41% COD reduction rate was obtained. Whereas the maximum removal rate for nitrate, ammoniacal nitrogen and phosphate was found to be 75%, 93.70% and 70.47%. Meanwhile, the MLSS and MLVSS showed 18mg/L and 22mg/L. The average difference of nitrate, ammoniacal nitrogen and phosphate contents present in the organic fertilizer made from Lemna minor was found to be ±95 mg/L, ±39.5mg/L and ±62.5mg/L when compared to other commercial fertilizers used in this study. The findings of this study shows that the use of macrophyte (Lemna minor) and microalgae (Chlamydomonas) resulted in a higher ability to remove the nutrients present in POME, which can contribute in improving the environment from pollution.